2016
DOI: 10.1007/s40615-016-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnic Differences in the Association Between Body Image Dissatisfaction and Binge Eating Disorder among Blacks

Abstract: Ethnic variation in the link between body image dissatisfaction and binge eating may be due to within-race cultural differences in body image between African Americans and Caribbean Blacks. This may include different definitions, norms, and expectations regarding the body size. Findings suggest that ethnicity may bias relevance of body image dissatisfaction as a diagnostic criterion for binge eating disorders among diverse populations of Blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
0
23
1
Order By: Relevance
“…Previous research has also shown that race, ethnicity, gender, and their intersections alter psychological correlates of obesity [22,26,29,30]. Differences in psychosocial determinants of obesity between African American males, African American females, Caribbean Black males, and Caribbean Black females have been previously reported [17,20,28]. …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research has also shown that race, ethnicity, gender, and their intersections alter psychological correlates of obesity [22,26,29,30]. Differences in psychosocial determinants of obesity between African American males, African American females, Caribbean Black males, and Caribbean Black females have been previously reported [17,20,28]. …”
Section: Discussionmentioning
confidence: 90%
“…Research has shown that race, ethnicity, gender, and their intersections alter psychosocial determinants of obesity [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Ethnic groups, for example, differ in the salience of psychosocial factors on obesity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported cross‐sectional findings ( n = 17; 44.7%) (Azarbad et al, ; Cachelin et al, ; Fitzgibbon et al, ; Gayle et al, ; Harrington et al, ; Harrington et al, ; Higgins et al, ; Hrabosky & Grilo, ; Jarosz et al, ; Kelly, Cotter, & Mazzeo, ; Lydecker et al, ; Lydecker & Grilo, ; Mazzeo et al, ; Mitchell & Mazzeo, ; Shuttlesworth & Zotter, ; Striegel‐Moore et al, ; Udo et al, ). Additional studies included secondary data analyses of cross‐sectional data ( n = 3; 7.8%) (Adamus‐Leach et al, ; Kelly et al, ; Wilson et al, ), secondary data analyses of population‐based longitudinal studies ( n = 4; 10.5%) (Marcus et al, ; Munn‐Chernoff et al, ; Smith et al, ; Striegel‐Moore et al, ); secondary analyses of large, representative data sets of Black respondents ( n = 4; 10.5%) (Assari, ; Blostein et al, ; Marques et al, ; Taylor et al, ), and secondary analyses of RCT's ( n = 3; 7.8%) (Lydecker et al, ; Mama et al, ; Thompson‐Brenner et al, ). The remaining studies were: (a) a focus group study (Scott et al, ); (b) case–control design studies ( n = 4; 10.3%) (Grilo et al, ; Pike et al, ; Striegel‐Moore et al, ; Striegel‐Moore et al, ); and (c) randomized clinical trials ( n = 2; 5.3%) examining the change in BE over time (Goode et al, ; Grilo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies examined racial differences in eating disorder pathology (e.g., concerns about weight, shape, restraint, as measured by the EDE) (Blostein et al, ; Grilo et al, ; Hrabosky & Grilo, ; Kelly et al, ; Kelly, Mitchell, et al, ; Lydecker & Grilo, ; Shuttlesworth & Zotter, ; Striegel‐Moore et al, ; Udo et al, ). In four of the nine studies (44%), no racial differences in ED psychopathology were observed, and Black and White women reported similar concerns about weight, shape, and eating (Grilo et al, ; Lydecker & Grilo, ; Striegel‐Moore et al, ; Udo et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation